Donum Grammaticorum: Festschrift für Harro Stammerjohann - Radatz, Hans-Ingo (De Gruyter, 2010)
In this festschrift marking the 65th birthday of the Chemnitz Romance studies scholar Harro Stammerjohann, 24 of his friends and colleagues deal with questions pertaining to French and Italian linguistic and literary history, general linguistics, and the didactics of French. A special birthday gift is a mazurka for piano composed by the American musicologist Mark DeVoto
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Bibliografie; Stammerjohann, Harro; Französisch; Italienisch